Contemporary challenges confronting school leaders - DiPaola, Michael F.; Forsyth, Patrick B. (Research and theory in educational administration., 2012)
Contemporary Challenges Confronting School Leaders is the eleventh in a series on research and theory dedicated to advancing our understanding of schools through empirical study and theoretical analysis. Consequently, the chapters include analyses that investigate relationships between school organizations and administrative practice that affect teacher and student effectiveness. This edition is organized around concepts that are significant to contemporary school leaders: student achievement and variables that contribute to it or influence achievement indirectly.